Karmic Ecology: Lessons from the Jain Dharma - Rankin, Aidan (The Trumpeter, 2009)
Jainism is one of the most ancient doctrines of the Indic tradition. Despite – or because of – its antiquity, it resonates well with modern concerns, in particular the concerns of the ecological movement. Jains attach high importance to the diversity and the intrinsic value of all life. They believe strongly in human reasoning and freedom of conscience for the individual. At the same time, they regard human creativity as conferring responsibilities rather than privileges, and the attempt to exercise unrestrained power as a sign of weakness rather than strength, one-sided ignorance rather than knowledge. The basis of Jainism is Ahimsa, which means non-violence or the conduct of social relationships in ways that consciously avoid harm. Jains extend the concept of society to the entire web of life, and human relationships with the rest of nature.The parallels between the Jain perspective and the perspective of Deep Ecology are fairly explicit. The distinctive Jain theory of karma is of interest to ecologists for tow principal reasons. First, it is based on the idea of a connecting web or network of life that corresponds with scientific understanding and ecological theory. Secondly, way of ‘living as if nature mattered’ through reducing negative human impact on the environment and working with rather than against the grain of nature. Jain doctrines of non-violence deeply influenced Mahatma Gandhi’s political thought and action. Today’s ecologists can also have their understanding enriched by this ancient source of wisdom.